Protecting Digital Twin-enabled 6G Networks for Industry 5.0 - Alcaraz-Tello, María Cristina; López-Muñoz, Francisco Javier (IEEE Network, 2023)
New industrial paradigms, such as the Industrial Internet of Things (IIoT) and Industry 5.0, are emerging in industrial contexts with the aim of fostering quality in operational processes. With the expected launch of 6G in the coming years, IIoT networks in Industry 5.0 ecosystems can leverage 6G technology and its support for training machine learning models using Digital Twins (DTs), embedded in DT Networks (DTNs), to transparently and continuously optimize their communications. Unfortunately, the use of these technologies, in turn, intensifies the attack surface and poses a serious threat to the new goals of Industry 5.0, such as improving the user experience, sustainability and resilience. This paper therefore proposes a layered protection framework for 6G-enabled IIoT environments, where not only DTs and DTNs are fully protected, but also the whole 6G ecosystem, complying with the expected goals of Industry 5.0. To achieve this, the framework identifies for each protection layer a set of security and privacy services to subsequently relate them to existing computing infrastructures (cloud, edge, edge-cloud) and provide the best approach for future IIoT deployments.
Keywords: Seguridad informática; Digital Twin Network; 6G; Industrial Internet of Things; Industry 5.0; Cybersecurity